MAKSIMISASI PENDAPATAN USAHA TANAMAN HIAS PALEM PADA CV. KEMBANG ASRI DI KOTA PALU - Tari, Dewi Sulis; Muis, Abdul; Laapo, Alimudin (AGROTEKBIS, 2018)
The purpose of this study was to determine the maximum revenue ornamental plant business in CV. Kembang Asri in the city of Palu. The number of respondents interviewed in this study as many as 9 out of 6 respondents consisted of the owner and two employees CV. Kembang Asri. Method used in determining the sample is purposive. The analysis used in this research is the analysis of linear programming with the aim to maximize the revenue palm plant species that red palm, palm and palm yellow daughter, the results showed revenue received CV. Kembang Asri for three types of plants i.e. red palm, palm and palm yellow daughter Rp. 5,950,649 Based on the results of the data analysis of the three types of ornamental plants: Plant red palm, palm and palm yellow daughter can generate maximum revenue of Rp. 5,982,524. The combination of plant type to get the maximum is by selling palm daughter that initially only 75 trees to 76 trees for trees yellow palm tree sold decreased by 54 to 52 trees and to plant red palm unchanged.